Determinan Lama Usaha dan Brand Lokal terhadap Minat Beli Warga Lokal di Tangerang: Studi pada Preferensi dan Keputusan Konsumen (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to examine the influence of business duration and local brand strength on local residents' purchasing interest in Tangerang City. In the context of global competition and the dominance of national and international brands, local brands face significant challenges to remain viable and in demand by the public. Therefore, understanding the factors that influence people's purchasing decisions towards local brands is crucial, especially in urban areas such as Tangerang that have social diversity and high levels of market competition. This study uses an explanatory quantitative approach, with data collected through questionnaires from 100 respondents aged 18–45 who have purchased products from local brands. Data analysis was conducted using the Partial Least Square (PLS) method to test the validity, reliability, and relationships between variables in the research model. The independent variables in this study are business duration and local brands, while the dependent variable is local residents' purchasing interest. The results show that local brands have a very significant and strong influence on local residents' purchasing interest, with a coefficient value of 0.700 and a large influence level (f² = 1.238). Meanwhile, business duration also had a significant effect, but its contribution was smaller (coefficient 0.232 and f² = 0.136). Simultaneously, the two variables explained 71.7% of the variation in local residents' purchasing intention (Adjusted R² = 0.717), indicating that the combination of business duration and local brand strength is an important determinant in shaping consumer preferences. This study recommends that local businesses focus on strengthening consistent branding strategies based on local identity, while maintaining business sustainability through continuous innovation. Local governments are also encouraged to support training for MSMEs in building strong and relevant brands.